Uji Efek Nefroprotektif Ekstrak Buah Kersen (Muntingia calabura) terhadap Kadar Blood Urea Nitrogen (BUN), Albumin, dan Ureum pada Tikus Putih yang Diinduksi Gentamisin - Juliana Hasan; Asyrun Alkhairi Lubis; Edy Fachrial (Lembaga Pengembangan Kinerja Dosen, 2026)
The antibiotic gentamicin has the potential to harm the kidneys by raising levels of oxidative stress, which in turn affects serum albumin and Blood Urea Nitrogen (BUN). Some of the antioxidant and nephroprotective properties found in cherry fruit (Muntingia calabura L.) include flavonoids, phenols, saponins, alkaloids, and triterpenoids. In this research, the purpose was to examine the impact of an ethanolic cherry fruit extract on the levels of albumin and BUN in male Wistar rats that had been treated with gentamicin. Thirty white rats were split into five groups for this experimental investigation. For 8 days, the normal group did not receive any therapy, the induction group took 100 mg/kgBW of gentamicin, and the treatment groups took 100, 200, or 400 mg/kgBW of cherry fruit extract orally in addition to the gentamicin induction. We used enzymatic techniques with UV-Vis spectrophotometry to assess the levels of BUN and albumin. A decrease in kidney function, as shown by changes in albumin and BUN levels, was seen after gentamicin therapy. When compared to the gentamicin group, the kidney function of the cherry fruit extract group was shown to be somewhat improved at dosages of 100, 200, and 400 mg/kgBW. There were no statistically significant changes in albumin or BUN levels brought about by the extract, according to the study. Finally, although cherry fruit (Muntingia calabura L.) ethanolic extract showed promise in describing its effects on kidney function maintenance, it has failed to establish statistically significant efficacy as a nephroprotective drug.